2011
DOI: 10.1002/ajmg.a.33972
|View full text |Cite
|
Sign up to set email alerts
|

A deleterious mutation in the LOXHD1 gene causes autosomal recessive hearing loss in Ashkenazi Jews

Abstract: Autosomal recessive nonsyndromic sensorineural hearing loss (ARNSHL) in Ashkenazi Jews, is mainly caused by mutations in the GJB2 and GJB6 genes. Here we describe a novel homozygous mutation of the LOXHD1 gene resulting in a premature stop codon (R1572X) in nine patients of Ashkenazi Jewish origin who had severe-profound congenital non-progressive ARNSHL and benefited from cochlear implants. Upon screening for the mutation among 719 anonymous Ashkenazi-Jews we detected four carriers, indicating a carrier rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 12 publications
4
29
0
Order By: Relevance
“…Vozzi et al reported three patients, in a consanguineous family, who had early-onset progressive SNHL, which was differed in degree in spite of having the same genotype; homozygous nonsense alleles (c.1588G>T, p.E530X) [3]. On the other hand, non-progressive congenital SNHL was also reported in other homozygous nonsense alleles (c.4714C>T, p.R1572X) [4]. In samba mice, a homozygous missense mutation in Loxhd1 caused profound deafness shortly after birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vozzi et al reported three patients, in a consanguineous family, who had early-onset progressive SNHL, which was differed in degree in spite of having the same genotype; homozygous nonsense alleles (c.1588G>T, p.E530X) [3]. On the other hand, non-progressive congenital SNHL was also reported in other homozygous nonsense alleles (c.4714C>T, p.R1572X) [4]. In samba mice, a homozygous missense mutation in Loxhd1 caused profound deafness shortly after birth.…”
Section: Discussionmentioning
confidence: 99%
“…SNHL, caused by the mutations in LOXHD1 , had a phenotypic feature showing progressive hearing loss at mid to high frequencies during childhood [2,3]. On the other hand, non-progressive congenital profound hearing loss has been reported as well [4]. …”
Section: Introductionmentioning
confidence: 99%
“…This could either lead to a protein lacking 10 PLAT domains or nonsense mediated decay of the transcript could lead to absence of LOXHD1. In contrast, the only other mutation reported in LOXHD1 is a founder mutation, p.R1572X, in the Ashkenazi Jews and causes prelingual profound degree of deafness (Edvardson et al, 2011).…”
Section: Loxhd1 (Dfnb77)mentioning
confidence: 95%
“…These genes include GJB6, PCDH15, USH1C, MYO3A, SLC26A4, LOXHD1, CDH23, MYO15A, WFS1, TECTA, POU4F3 and the inverted duplication of TJP2. 3,[23][24][25] All known deafness-causing mutations in the Palestinian population were excluded, including mutations in CDH23, MYO7A, MYO15A, OTOF, PJVK, SLC26A4, TECTA, TMHS, TMPRSS3, OTOA, PTPRQ and GPSM2. 22,26,27 Massive parallel sequencing Capture libraries were created and MPS was performed, followed by bioinformatics analysis, as previously described.…”
Section: Gene Exclusionmentioning
confidence: 99%